2005
DOI: 10.1021/cg0503503
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Nanostructures from Layered Manganese Oxide

Abstract: In this paper, we report the preparation of one-dimensional (1D) nanostructures from layered compounds (2D). γ-MnOOH nanorods were successfully prepared from platelike layered Na-birnessite by simple hydro(solvo)thermal treatment at low temperature. It was observed that the reaction medium plays an important role in the phase and morphology modifications. The γ-MnOOH was thermally treated under different conditions of atmosphere (inert or oxidizing) and temperature, which led to several phases of manganese oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…Once a pristine MnO x phase is obtained, it is possible to synthesize a different polymorph from it by using different treatments. By using this approach and inspired by the work of Ferreira et al.,50 we prepared β‐MnO 2 on carbon starting from the orthorhombic δ‐MnO 2 /C synthesized according to Equation (2). [Notably, hexagonal δ‐MnO 2 /C prepared according to Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Once a pristine MnO x phase is obtained, it is possible to synthesize a different polymorph from it by using different treatments. By using this approach and inspired by the work of Ferreira et al.,50 we prepared β‐MnO 2 on carbon starting from the orthorhombic δ‐MnO 2 /C synthesized according to Equation (2). [Notably, hexagonal δ‐MnO 2 /C prepared according to Eq.…”
Section: Resultsmentioning
confidence: 99%
“…According to line S2 in Fig. 1, all the diffraction peaks can be indexed to the mixtures form of birnessite (JCPDS 23-1046) [22], tetragonal hausmannite structure (space group I41/amd) of Mn 3 O 4 with lattice constants of a = b = 5.762 Å, and c = 9.470 Å (JCPDS 24-0734) [9,37], and bixbyite (space group pcbb/61) of Mn 2 O 3 with lattice constants of a = 9.416 Å, b = 9.424 Å, and c = 9.405 Å (JCPDS 24-0508) [38][39][40]. All the XRD results show the components of the structures and potential chemical changes take place in both the Baeyer reaction and thermal treatment.…”
Section: Methylene Blue (Mb) Adsorptionmentioning
confidence: 99%
“…Via the same reaction as Wang et al and with the assistance of silver foil or silver cation catalyst, Li et al [31] prepared α-MnO 2 at room temperature, obtaining β-MnO 2 hydrothermally at 80 • C. In addition, Subramanian et al [32] In addition, obtaining one polymorph from another was another strategy; for example, Wei et al [33] successfully transformed γ -MnO 2 into αand β-MnO 2 at 140 and 170 • C, respectively. Ferreira et al [34] employed hydrothermal transformation in a dodecylamine aqueous solution, from δ-MnO 2 into MnOOH, which can be subsequently annealed at 300-500 • C to form β-MnO 2 . In addition, Shen et al [26] reported a transformation from δ-MnO 2 into other polymorphs of MnO 2 with (2 × 4), (2 × 3) and (1 × 1) tunnel structure at pH = 13, 7 and 1, respectively; the pH value is believed to affect the formation of polymorphs significantly.…”
Section: Introductionmentioning
confidence: 99%